Brand extension evaluation: real world and virtual world. Issue 7 (11th November 2014) - Ramanathan, Jayasankar; Purani, Keyoor
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to help marketing scholars view virtual worlds as new product–markets and trigger serious investigations on consumer evaluation of brand extensions when a brand is extended from the real world to a virtual world and vice versa. Design/methodology/approach – The paper makes an extensive review of studies on virtual world. Further, it amalgamates understanding from well-established literature on consumer evaluation of brand extensions into the emerging virtual world understanding to conceptualize moderating influence of contexts – the real world context and a virtual world context – on how consumers evaluate brand extensions. Findings – Through logical arguments supported by existing literature, the paper provides 14 well-conceptualized propositions that argue that the real world and virtual world contexts moderate the well-established relationships in brand extension literature. It broadly proposes that the relationships between the consumer evaluations of brand extension and its known determinants are stronger in case of within-the-world extensions and weaker in case of across-the-world extensions. Research limitations/implications – The paper introduces to the marketing scholars an entirely new area of enquiry as it challenges the known brand extension knowledge when a brand is extended across the worlds. Practical implications – Marketers considering launching new offerings across the contexts of real or virtual world would have implications on whether to extend the brand or not. Originality/value – Virtual worlds have largely been construed in marketing literature as fictional worlds. There is not much explored in terms of virtual worlds as new product–markets. The study offers unique value in conceptualizing differences among within-the-world brand extensions and across-the-world brand extensions.